The Mediating Role of Brand Love between Brand Experience Dimensions and Word-of-Mouth Relationship: A Student Perspective of Smart Gadgets - Roskruge, Zodwa; Chinomona, Richard; Mapuranga, Miston (International Review of Management and Marketing, 2025)
The purpose of this study was to investigate how university students who use smart devices perceive brand love as a mediating factor between brand experience qualities and word-of-mouth. To achieve its objective, the research study employed a cross-sectional research design that was based on positivism as a paradigm and a quantitative technique. Purposive and snowball sampling methods were used to choose 300 participants to receive a fully structured, self-administered questionnaire. Students of Walter Sisulu University in Mthatha were the participants, and data were collected using an online questionnaire. The key findings under Smart PLS revealed that all hypothesised relationships are positive in a significant way. However, the association between Word-of-Mouth and Brand Love was determined to be the strongest with a path coefficient of β = 0,861; t = 43,613; p = 0.000, while the relationship between Affective Experience and Brand Love was the poorest, determined by a path coefficient of β = 0,374, t = 5,118, p = 0,000, while still favourable. Policymakers should provide extra clear instructions on how to use smart gadgets, as not only young people use smart gadgets. The results of the research will help businesses selling smart gadgets make informed decisions regarding their marketing plans. Marketers who have an interest in segmenting the markets will benefit from controlling the consumer demographic traits. The results suggest that brand experience and word-of-mouth marketing are suitable direct marketing channels or dimensions which customers have become most familiar with to truly fall in love with the brand.